Interhemispheric Asymmetry in the High‐Latitude Neutral Density Variations During the 13–14 March 2022 Storm - Qingyu Zhu; Gang Lu; Sarah Vines; Marc Hairston (Space Weather)
Abstract During the second recovery phase of the 13–14 March 2022 storm, intense high‐latitude neutral mass density spikes are detected by satellites at ∼500 km in both hemispheres. These density spikes, accurately modeled by the Global Ionospheric Thermosphere Model (GITM), are identified as high‐latitude neutral mass density anomalies (HDAs). The GITM simulation indicates that these HDAs, which extends over the polar region, are important features in high‐latitude neutral density. Furthermore, GITM reveals that these HDAs are manifestations of transpolar traveling atmospheric disturbances triggered on the dawn side. Moreover, GITM also reveals significant interhemispheric asymmetries (IHAs) in the magnitude, propagation speed, and propagation direction of HDAs, which are linked to the IHAs in the distribution and magnitude of Joule heating deposited as well as the thermospheric background conditions. This study presents a dynamic perspective on the IHA of storm‐time high‐latitude neutral density variations that is particularly helpful to the proper interpretation of satellite observations.